Marriage Registration Assistance According to Law No. 1 of 1974 on Marriage - Sobardo Hamonangan; Mulyadi, Dudi; Kadir Katjong; Supriyanto Hadi; Frans Reumi (PT. ALHAFI BERKAH INDONESIA, 2024)
The title of this community service program is